Kelas Ibu Hamil terhadap Pengetahuan Ibu tentang Kesehatan Ibu dan Anak - Sellvinia Azulla; Vinami Yulian (Jurnal Keperawatan Silampari, 2023)
This study aims to determine the influence of pregnant women's classes on mothers' knowledge about maternal and child health. This study uses the literature review method. The databases used to obtain journal articles are Google Scholar, PubMed, and SINTA. The results of this study indicate that the mother's class influences the mother's knowledge about maternal and child health. A supporting factor in organizing courses for pregnant women is using video media to help mothers absorb information better. The inhibiting factors were the period for carrying out classes for pregnant women, mothers who had not given birth to their babies, unusual practices, health care providers, and relatives. Simply put, the pregnant women's class influences mothers' knowledge about maternal and child health. In practice, there are supporting and inhibiting factors for mothers in implementing the material for pregnant women's classes. Keywords: Pregnant Women's Class, Maternal and Child Health, Mother's Knowledge